2021
DOI: 10.3389/fimmu.2021.724429
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of CD86+/CD163+ Macrophages Predicts Postoperative Recurrence in Stage II-III Colorectal Cancer

Abstract: Tumor-associated macrophages (TAMs) are pivotal for tumor progression and metastasis. We investigated the stromal CD86+TAM/CD163+TAM (CD86/CD163) ratio as a novel prognostic biomarker for stage II-III colorectal cancer (CRC). Two independently clinical cohorts of stage II-III CRC were retrospectively enrolled in this study. TAMs were detected using immunohistochemical staining for CD86 and CD163. The stromal CD86/CD163 ratio was calculated as a prognostic biomarker for recurrence-free survival (RFS) and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…The results of previous studies suggest that age, TNM stage, pathological tumour grading, and CEA all in uence the prognosis of CRC patients [10][11][12] , which is in agreement with the ndings in this study that patients characterized by age ≤ 65 years, TNM stage I-II, pathological high/moderate differentiation, and CEA < 5 µg/L had a longer OS. This study nally revealed that AAPR is a new effective predictor of postoperative prognosis in CRC patients (its AUC = 0.730 for ROC is greater than the AUC = 0.659 for TNM staging ROC).…”
Section: Discussionsupporting
confidence: 93%
“…The results of previous studies suggest that age, TNM stage, pathological tumour grading, and CEA all in uence the prognosis of CRC patients [10][11][12] , which is in agreement with the ndings in this study that patients characterized by age ≤ 65 years, TNM stage I-II, pathological high/moderate differentiation, and CEA < 5 µg/L had a longer OS. This study nally revealed that AAPR is a new effective predictor of postoperative prognosis in CRC patients (its AUC = 0.730 for ROC is greater than the AUC = 0.659 for TNM staging ROC).…”
Section: Discussionsupporting
confidence: 93%
“…Subsequently, univariate and multifactorial analyses were performed, and survival curves for 5-year OS were plotted. The results of previous studies suggest that age, TNM stage, pathological tumor grading, and CEA all influence the prognosis of CRC patients, [10][11][12] which is in agreement with the findings in this study that patients characterized by age ≤65 years, TNM stage I-II, pathological high/moderate differentiation, and CEA <5 μg/L had a longer OS. This study finally revealed that AAPR is a new effective predictor of postoperative prognosis in CRC patients (its AUC = .730 for ROC is greater than the AUC = .659 for TNM staging ROC).…”
Section: Discussionsupporting
confidence: 92%
“…The baseline demographic and clinical characteristics were comprehensively evaluated and compared according to disease severity (with progression versus without progression) and survival outcome (survival versus death). The optimal cutoff value for continuous variables was calculated using the Maxstat algorithm [ 12 ]. Categorical variables were compared according to chi-squared test or Fisher’s exact test.…”
Section: Methodsmentioning
confidence: 99%